PENGARUH KUALITAS PELAYANAN DAN MUTU PRODUK TERHADAP KEPUASAN KONSUMEN PADA WELLTEA DI BELAWA KABUPATEN WAJO - Ahmad Jayadi; Andi Riska Andreani Syafaruddin; Rahman Yakub; Inna Mutmainna Cahyani Thahir (Journal of Economic, Bussines and Accounting (COSTING), 2026)
The growth of the contemporary beverage industry in Indonesia has shown rapid development, marked by the increasing number of modern beverage businesses that have become a trend among society, especially young consumers. The increasingly competitive business environment makes service quality and product quality important factors in creating customer satisfaction. This study aims to analyze the effect of service quality and product quality on customer satisfaction at WellTea in Belawa, Wajo Regency. This research employed a quantitative approach using descriptive and verificative methods. The research sample consisted of 96 respondents determined using the Lemeshow formula with a non-probability sampling technique. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression with the assistance of IBM SPSS version 27. The results showed that partially, service quality had a positive and significant effect on customer satisfaction with a significance value of 0.005 < 0.05. Product quality also had a positive and significant effect on customer satisfaction with a significance value of 0.000 < 0.05. Simultaneously, service quality and product quality significantly affected customer satisfaction, as indicated by the F-test significance value of 0.000 < 0.05. The R Square value of 0.860 indicates that 86.0% of the variation in customer satisfaction can be explained by service quality and product quality, while the remaining 14.0% is influenced by other variables outside this study.